2006
DOI: 10.1167/iovs.05-1430
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofCFH,TLR4, andAPOEPolymorphism in India Suggests the Tyr402His Variant ofCFHto be a Global Marker for Age-Related Macular Degeneration

Abstract: The CFH polymorphism Tyr402His appears indicative of AMD pathogenesis. Diabetes, age, and gender in the presence of the homozygous "CC" genotype in CFH carry an increased risk of AMD. Hence this polymorphism could be used as a potential marker for predictive testing across continents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 41 publications
6
48
1
2
Order By: Relevance
“…These results have been replicated in other studies [112,113,114,115,116,117,118,119,120,121,122] and confirmed by a meta-analysis [123]. However, likely because of the weak allele effects of Apo-ε, and because of the low allele frequencies of both the ε2 and ε4 alleles, some studies could not demonstrate any association between this gene and AMD [124,125,126,127,128,129].…”
Section: Genetic Factors Associated With Amdsupporting
confidence: 78%
“…These results have been replicated in other studies [112,113,114,115,116,117,118,119,120,121,122] and confirmed by a meta-analysis [123]. However, likely because of the weak allele effects of Apo-ε, and because of the low allele frequencies of both the ε2 and ε4 alleles, some studies could not demonstrate any association between this gene and AMD [124,125,126,127,128,129].…”
Section: Genetic Factors Associated With Amdsupporting
confidence: 78%
“…Both CFH and FHL-1 are present in vitreous fluid of eye and expressed by RPE cells (Skerka et al, 2007). A tyrosine to histidine mutation at codon 402 (Y402H) within CFH is strongly associated with AMD pathology (Rivera et al, 2005;Klein et al, 2005;Edwards et al, 2005;Haines et al, 2005;Hageman et al, 2005) and has been suggested to be a global marker for AMD (Kaur et al, 2006). The tyrosine residue at position (CFH YY402 ) is considered as protective variant whereas the histidine residue at this position (CFH YH402 and CFH HH402 ) a risk variant for AMD.…”
Section: Complement and Age-related Macular Degenerationmentioning
confidence: 99%
“…Interestingly, Zareparsi et al reported an association of Toll-like receptor 4 and AMD 35 , in contradistinction to atherosclerosis, where this seems to induce protection. However, in an evaluation of a cohort of AMD patients in India, no association was found with Toll-receptor 4, while one was found with complement factor H. 36 …”
Section: Other Genesmentioning
confidence: 97%